Koreksi Pengaruh Lereng Terhadap Nilai Spektral Tanaman Karet Pada Citra Landsat Thematic Mapper = Correction of Slope Influence in Spectral Values of Rubber Plantation On Landsat Thematic Mapper Image - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The main objectives of this research are (1) to analyze the influence of slope on spectral values of rubber plantation on Landsat TM digital data, (ii) to ascertain the effect of slope correction on Landsat TM digital data. Slope factor which was used in this research are aspect of slope and steepness of slope. The selected area of this rep.Parch is the western part of Semarang, Central Java Province. This research used Landsat TM remotely sensed optical data (band 1, 2, 3, 4, 5, and 7), which was recorded on 20th of June 1996, with level of correction 5. The other data was topographic maps scalelated to 1:50,000. Digital Elevation Model (DEM) was derived to aspect map and slope map based on topographic map. In a standard of radiometric correction which is usually applied in the stage of pre-processing, the influence of slope in spectral values hasn't been corrected. To find out the influence of slope in spectral values on rubber plant, it can be analyzed by 'statistical method. To reduce the influence of slope, this research used some methods of correction: (a) Lambertian, (b) Cosine Correction, (c) The Minnaert Correction, and (d) Non-Lambertian... The result of this resarch showed that the difference of slope causes spectral values of rubber plantation varies. The application of slope correction to spectral values of Landsat TM image showed that Non-Lambertian model is the best method of correction in this research.